2008
DOI: 10.1021/es801763g
|View full text |Cite
|
Sign up to set email alerts
|

Batteryless, Wireless Sensor Powered by a Sediment Microbial Fuel Cell

Abstract: Sediment microbial fuel cells (SMFCs) are considered to be an alternative renewable power source for remote monitoring. There are two main challenges to using SMFCs as power sources: 1) a SMFC produces a low potential at which most sensor electronics do not operate, and 2) a SMFC cannot provide continuous power, so energy from the SMFC must be stored and then used to repower sensor electronics intermittently. In this study, we developed a SMFC and a power management system (PMS) to power a batteryless, wireles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
177
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(182 citation statements)
references
References 23 publications
1
177
1
3
Order By: Relevance
“…This also could lead to sediment MFCs being situated in areas of high organic flux, such as underneath fish farms or sites of agricultural run off, which could provide an increase in organics for oxidation of the MFCs. To power devices requiring higher power levels than the MFCs are currently capable of producing, MFCs have been linked to charge capacitors to provide brief bursts of increased power which is slowly recharged by the MFC [14,15]. These have the advantage that charge can be stored and supplied intermittently at a level higher than that of the MFC.…”
Section: Current Applications For Microbial Fuel Cellsmentioning
confidence: 99%
“…This also could lead to sediment MFCs being situated in areas of high organic flux, such as underneath fish farms or sites of agricultural run off, which could provide an increase in organics for oxidation of the MFCs. To power devices requiring higher power levels than the MFCs are currently capable of producing, MFCs have been linked to charge capacitors to provide brief bursts of increased power which is slowly recharged by the MFC [14,15]. These have the advantage that charge can be stored and supplied intermittently at a level higher than that of the MFC.…”
Section: Current Applications For Microbial Fuel Cellsmentioning
confidence: 99%
“…In BESs, microorganisms catalyze the electrochemical formation or degradation of organic molecules by interfacing their biological metabolism with an electrode 1, 2, 3. The interaction between microorganisms and electrical conductive structures makes these systems unique and versatile, with potential applications in electrical energy storage,4, 5 energy‐ and nutrient‐recovering wastewater treatment systems,6, 7, 8 production of high‐value chemical commodities,9, 10 long‐term off‐grid low‐power electricity generation,11, 12 and the development of highly specific and innovative biosensors 13, 14. Additionally, microorganisms may provide temporal charge storage within the microbial cell 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolved oxygen (DO) is crucial for the cathodic reaction, and therefore SMFC is typically installed in shallow waters [118]. Previous studies have demonstrated that SMFCs can produce electricity and supply power to wireless sensors in both marine and fresh-water environments [113,119,120]. Capacitors have been adopted to accumulate energy generated from MFCs [121][122][123][124].…”
Section: Bes For Agricultural Monitoringmentioning
confidence: 99%
“…They can be installed in wetlands, rivers or lakes near the farmland. To use the electricity, the output potentials must be boosted and operated by DC-DC converters and a PMS [119,120]. In the area where open water is not available, soil MFCs [130][131][132][133] or plant MFCs [134,135] may be applied.…”
Section: Bes For Agricultural Monitoringmentioning
confidence: 99%